Masculinity cues, perceptions of politician attributes, and political behavior*. (4th September 2020) - Chan, Ho Fai; Skali, Ahmed; Stadelmann, David; Torgler, Benno; Whyte, Stephen
Abstract: How are masculine‐looking politicians perceived by voters? Are these judgments accurate? We asked Australian survey participants to rate images of unknown‐to‐them Swiss politicians. We find that politicians with prominent markers of masculinity (including facial hair, baldness, and higher facial width‐to‐height ratio) are perceived as less honest and competent. To determine whether these perceptions correlate with political behavior, we exploit two unique features of Swiss politics. First, to check for politician–voter congruence, we match each politician's voting record to that of their constituents on identically worded legislative proposals. We find that bearded politicians are less likely to behave according to constituents' preferences. Second, by exploiting the mandatory disclosure of lobby group affiliations, we show that bearded politicians are less likely to be captured by interest groups. Our results suggest that more masculine‐looking politicians are recognized by both voters and lobby groups as less amenable to being controlled.